Pengaruh Pijat Laktasi Terhadap Produksi ASI Pada Ibu Menyusui Di Kelurahan Sendang Sari Kabupaten Asahan Tahun 2019 - Nani Jahriani (Excellent Midwifery Journal, 2019)
Mother's Milk (ASI) is a natural nutrient for babies with the most suitable nutritional content for optimal growth. Decreased milk production in breastfeeding mothers is one of the reasons for not materializing exclusive breastfeeding for the first 0-6 months of the baby's life and continued breastfeeding for children until ≥ 2 years, so the mother will give MP-ASI in the form of formula milk. Formula milk does not have complete contents like breast milk, and does not contain antibodies like those contained in breast milk. This causes babies who do not get exclusive breastfeeding will easily get sick. Some mothers experience difficulties and failure to breastfeed because the milk has not come out yet, a little breast milk or blasted nipples makes the mother afraid to breastfeed. So that mothers need special breast care to facilitate the lactation process. Lactation massage is one of the painless breast care methods that can stimulate the strength of the breast muscles to increase milk production and make the breasts softer and more elastic so that it makes it easy for babies to suck breast milk.  Lactation massage will also provide a sense of relief and overall comfort for the mother, improve the quality of breast milk, prevent blisters and mastitis and can improve / reduce lactation problems caused by flat nipples, inverted nipples. In Sendang Sari sub-district, Asahan Regency, the problem of decreased milk production and less is one of the problems in the process of breastfeeding mothers. This was obtained from the results of interviews with mothers who complained their babies were still fussy even though they were breastfeeding, so mothers gave additional formula milk to meet the needs of their babies.